Work environments : spatial concepts, usage strategies, communications - Schittich, Christian (In detail., 2011)
Presents the various work environments organized according to use and provides model solutions presented from floor plan to details. From offices to laboratories, archives, and libraries all the way to mobile research stations, the focus throughout is on the successful interplay between technical standards, organizational structures, and human needs.